Synthesis and characterization of xerogel from Palm Kernel Shell Biochar / Nor Mohd Razif Noraini ... [et al.] - Noraini, Nor Mohd Razif; Alias, Azil Bahari Alias; Qarizada, Deana; Md Azman, Farah Aida; Abdul Rashid, Zulkifli; Che Hasan, Mohd Rosdi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
With an alarming amount of agricultural waste disposal rate, it emerges the search to utilize biomass and turn them into a beneficial product. Biochar is one the beneficial product that contains high carbonaceous material that is commonly utilized as an adsorbent. This research aims to characterize and produce xerogel from Palm Kernel Shell (PKS) biochar. The production of Biochar Xerogel was produced through the sol-gel method and further dried in an oven to produce xerogel. The synthesized xerogel was characterized using different characterization techniques which are Fourier Transform Infrared Spectroscopy (FTIR), Brunauer-Emmett and Teller (BET), Scanned Electron Microscopy (SEM) analysis, Thermogravimetric analysis (TGA) and X-Ray Diffraction (XRD). The FTIR spectrum analysis has shown the existence of various functional groups such as hydroxyl, aldehyde, alkane and aromatic groups. The TGA analysis reveals the maximum thermal of 1000 °C for xerogel and XRD patterns reveal the amorphous nature of the extracted xerogel biochar.